1971
DOI: 10.1111/j.1469-8137.1971.tb04583.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase Activity of Intact Young Wheat Roots Under Sterile and Nonsterile Conditions

Abstract: Summary In assays of acid phosphatase activity with p‐nitrophenyl phosphate as substrate, the low activity found in fluids removed from around roots in liquid medium was not affected by the presence of micro‐organisms. Most phosphatase activity of intact seedling roots was associated with the root surface and was not increased by micro‐organisms in the rhizoplane; in some experiments activity was significantly reduced by soil micro‐organisms. Inoculation of roots with pure cultures of bacteria and a fungus kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

1973
1973
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(29 citation statements)
references
References 17 publications
1
26
0
2
Order By: Relevance
“…The Apase secreted from soil microorganisms is also capable of catalyzing the mineralization of organic phosphate (Ridge and Rovira 1971). However, the Apase from plant roots is secreted to the rhizosphere which is very close to the root surface.…”
Section: Resultsmentioning
confidence: 99%
“…The Apase secreted from soil microorganisms is also capable of catalyzing the mineralization of organic phosphate (Ridge and Rovira 1971). However, the Apase from plant roots is secreted to the rhizosphere which is very close to the root surface.…”
Section: Resultsmentioning
confidence: 99%
“…Acid phosphatases produced by the ectomycorrhizal fungal mantle and the attached ramifying mycelium are believed to catalyze the hydrolysis of complex organic phosphorus compounds into more readily absorbed forms (Ho & Zak, 1979). Ridge & Rovira (1971) indicated that root surface phosphatases may be more important in the organic P mineralization than enzymes in the aqueous phase or bound to the surrounding soil. Antibus et al (1981) showed that the acid phosphatase activity of ectomycorrhizal roots of Salix rotundifolia Trautv.…”
Section: Introductionmentioning
confidence: 99%
“…Ridge and Rovira, 1971), metabolism by mycorrhizas (e.g. Murdoch, Jackobs and Gerdemann, 1967) and rhizosphere organisms (e.g.…”
Section: Possible Functionsmentioning
confidence: 99%